Need Help?

Subscribe to Differential Equation

  • Notes
  • Comments & Questions

Suppose that $$f(s)=L[F(t)]$$ exists $$, s>0 .$$ Show that if $$c$$ is positive constant then $$L(F(c t))=\frac{1}{c} F\left(\frac{s}{c}\right)$$

$$L(f(ct))=\int_{0}^{\infty} e^{-s t} F(c t) d t$$

$$U=c t \quad \rightarrow d u=c d t$$

$$\int_{0}^{\infty} e^{-s \frac{u}{c}} F(u) \frac{d u}{c}=\frac{1}{c} \int_{0}^{\infty} e^{-\frac{s}{c} u} F(u) d u$$

$$=\frac{1}{c} \cdot F\left(\frac{s}{c}\right)$$

Prove that if $$L\{F(t)\}=f(s)$$ then $$L\left\{\mathrm{e}^{a t} F(b t)\right\}=\frac{1}{b} f\left(\frac{s-a}{b}\right), b>0$$

$$L\left\{e^{a t} F(b t)\right\}=\int_{0}^{\infty} e^{-s t} \cdot e^{at} F(b t) d t$$

$$=\int_{0}^{\infty} e^{-(s-a) t} F(b t) d t \neq f(s-a)$$

put $$u=b t \rightarrow d u=b d t$$

$$\int_{0}^{\infty} e^{-(s-a) \frac{u}{b}} F(u) \frac{1}{b} d u=\frac{1}{b} \int_{0}^{\infty} e^{-\left(\frac{s-a}{b}\right) u} F(u) d u$$

$$=\frac{1}{b} f\left(\frac{s-a}{b}\right), b>0$$

No comments yet

Join the conversation

Join Notatee Today!